Effectiveness of forward freight agreements in mitigating capesize ship-owners' business risk between 2009 and 2014 - Lim, Kai Liang (2016)
Shipowners have employed various risk management tools to reduce their exposure in the inherently risky freight market to ensure survival. Traditionally, they utilize physical hedging tools such as Time Charters (TC) to hedge their earnings. The advent of Forward Freight Agreements (FFA), a paper hedge, provides shipowners with an alternative tool to reduce their risk through the financial market. This paper aims to investigate which hedging tool is more effective in helping shipowners mitigate their business risk. This paper first discusses extensively on the various risks facing a shipowner and how can FFA reduce their business risk. This paper then adopts a quantitative approach and creates a corporate finance model to model the cash flow of a real-life practical shipowner. Using publicly available information from Clarkson Intelligence Network, Bloomberg, and Moores Stephen OpsCost, the model simulates the financial performance of a shipowner acquiring Capesize Vessels through various acquisition methods and deploying them. The risk and returns derived from the various deployment and is then determined and compared with that of FFA over the period of 2009-2014. Overall, utilising +1CAL FFAs as an hedge it was found that FFA proved to be possible hedge as it generated consistently better returns as compared to a vessel working solely in the spot market. However, TC are more effective than FFA as a hedging tool as the returns from the asset classes hedged with TC are far superior than that of FFA. This study provides a structure with objective metrics of measurement for future investigation of other hedging tools on their effectiveness.